Time-efficient and computer-guided sprint interval exercise training for improving health in the workplace: a randomised mixed-methods feasibility study in office-based employees - Richard S. Metcalfe; Hady Atef; Kelly Mackintosh; Melitta McNarry; Gemma Ryde; Denise M. Hill; Niels B. J. Vollaard (BMC, 2020)
Abstract Background The efficacy of high-intensity interval training (HIT) as a time-efficient exercise strategy for beneficially modifying risk factors for cardiovascular disease has repeatedly been demonstrated in controlled laboratory settings. However, the effectiveness of HIT in an unsupervised workplace setting has not been investigated. The objective of this study was to use mixed methods to investigate the feasibility, acceptability and effectiveness of a short-duration, high-intensity exercise intervention (REHIT) when applied unsupervised in a workplace setting. Methods Twenty-five office-workers (mean ± SD age: 47 ± 9 y, BMI: 27.5 ± 4.4 kg·m− 2, V̇O2max: 28 ± 7 mL·kg− 1·min− 1) completed a 6-week REHIT intervention unsupervised in their workplace (n = 13, 6 men), or acted as a no-intervention control (n = 12, 6 men). The intervention consisted of 2 sessions/week of low-intensity (~ 25 W) cycling interspersed with 2 'all-out' sprints, increasing in duration from 10 to 20 s per sprint over the 6 weeks (total time-commitment: 8:40 min per session). V̇O2max was assessed pre- and post-training, whilst questionnaire-based measures of exercise enjoyment, self-efficacy, and acceptability were completed post-training. Eight participants also completed post-intervention semi-structured interviews. Results V̇O2max significantly improved in the exercise group (2.25 ± 0.75 L·min− 1 vs. 2.42 ± 0.82 L·min− 1; + 7.4%) compared to the control group (2.22 ± 0.72 L·min− 1 vs. 2.17 ± 0.74 L·min− 1; − 2.3%; time*intervention interaction effect: p < 0.01). Participants considered the REHIT intervention acceptable and enjoyable (PACES: 89 ± 17 out of 119) and were confident in their ability to continue to perform REHIT (7.8 ± 1.2 out of 9). Qualitative data revealed that REHIT offered a time-efficient opportunity to exercise, that was perceived as achievable, and which encouraged highly valued post-exercise outcomes (e.g. progress towards health/fitness benefits). Conclusions REHIT could be implemented as a feasible, effective and acceptable exercise intervention in a workplace setting, with a total time-commitment of < 20 min/week. Consideration of certain psycho-social factors and behaviour-change techniques may ensure adherence to the REHIT programme in the long term. Trial registration The study was registered on ClinicalTrials.gov on 07/05/2019 (registration: NCT03941145 ).